Cytotoxic activity of sanguinarine and dihydrosanguinarine in human promyelocytic leukemia HL-60 cells - Vrba, Jirí; Dolezel, Petr; Vicar, Jaroslav; Ulrichová, Jitka (Toxicology in vitro, 2009)
The benzo[c]phenanthridine alkaloid sanguinarine has been studied for its antiproliferative activity in many cell types. Almost nothing however, is known about the cytotoxic effects of dihydrosanguinarine, a metabolite of sanguinarine. We compared the cytotoxicity of sanguinarine and dihydrosanguinarine in human leukemia HL-60 cells. Sanguinarine produced a dose-dependent decline in cell viability with IC(50) (inhibitor concentration required for 50% inhibition of cell viability) of 0.9 microM as determined by MTT assay after 4h exposure. Dihydrosanguinarine showed much less cytotoxicity than sanguinarine: at the highest concentration tested (20 microM) and 24h exposure, dihydrosanguinarine decreased viability only to 52%. Cytotoxic effects of both alkaloids were accompanied by activation of the intrinsic apoptotic pathway since we observed the dissipation of mitochondrial membrane potential, induction of caspase-9 and -3 activities, the appearance of sub-G(1) DNA and loss of plasma membrane asymmetry. This aside, sanguinarine also increased the activity of caspase-8. As shown by flow cytometry using annexin V/propidium iodide staining, 0.5 microM sanguinarine induced apoptosis while 1-4 microM sanguinarine caused necrotic cell death. In contrast, dihydrosanguinarine at concentrations from 5 microM induced primarily necrosis, whereas apoptosis occurred at 10 microM and above. We conclude that both alkaloids may cause, depending on the alkaloid concentration, both necrosis and apoptosis of HL-60 cells.
Keywords: Benzophenanthridines; Cell Cycle; apoptóza; Caspases; Isoquinolines; membránový potenciál mitochondrií; kaspasy; viabilita buněk; Cell Survival; buněčný cyklus; benzofenantridiny; lidé; HL-60 Cells; isochinoliny; HL-60 buňky; Membrane Potential, Mitochondrial; Apoptosis; Humans